Media and religion: Rodja TV’s involvement in the civil society discourse for community development - Bakti, Andi Faisal (Penerbit Universiti Kebangsaan Malaysia, 2018)
After Soeharto’s fall in 1998, a plethora of different types of media discovered ways to grow and expand in Indonesia. After Indonesia accepted the democratic political system, freedom of expression became part of everyday life. As pillars of democracy, the media are the tools par excellence for the expression of the people’s ideas. Established in 2007, Rodja TV started its own discourse amidst civil society. The aim of this paper is to see the involvement of Rodja TV in the civil society discourse for community development. To what extent Rodja TV’s discourse has involved the four civil society spheres - private, public, market, and the state - and how it pursued the creation of the exemplified community it promotes. This paper takes the qualitative approach and uses data gathered from observation, documents, and interviews. Apparently, Rodja TV has adopted a safe discourse by showing its propensity for mainstream Sunni Islam rather than taking the jihadi approach to politics that strives for the establishment of an Islamic state. Rodja TV’s main targets are localism and globalism but it is open to local values and selected expressions of modernism. However, it does not criticise the Indonesian government in fighting terrorism. While the station initially targeted a limited audience, because it broadcasts information about Islamic tenets, its public audience widened and members of Muslim associations, businessmen, and members of the government have become attracted to Rodja TV’s programs.